STATUS CHANGE SIMULATION IN IDEAL GAS - FILIPEK, Josef (Trends in education, 2015)
In closed thermodynamic setup three magnitudes change with heating, cooling and external force effects - volume, pressure and temperature. Therefore it is suitable to visualize state changes in spatial diagram (on thermodynamic plane). Multimedia project, which is a base of this article, graphically describes the course of state and energy magnitudes in ideal gas.
Keywords: reversible changes in gas; state function; thermodynamic plane; Adobe flash; interactive animation .